Effect of Nutrients and Salinity on Growth of Temperate Mangroves (Avicennia marina var australasica) in Northern New Zealand - Gritcan, Iana (Auckland University of Technology, 2019)
Estuarine environmental conditions in New Zealand have changed greatly due to human catchment activity (e.g., deforestation, intensive agricultural activity, and urbanisation). These factors have led to additional accretion of sediment (sedimentation) and nutrients (eutrophication) throughout New Zealand waterways and coast waters. In recent years, New Zealand mangroves (Avicennia marina var australasica) have shifted their distribution within estuaries and rapidly spread into areas where they have never been found before. Many local communities and councils are worried that mangroves have replaced sandy bare tidal flats and other estuarine habitats (i.e., seagrass beds, marshlands) and will turn them into muddy sites. Researchers have proposed several reasons for the spread of temperate mangroves, including estuary infilling, increased nutrient inputs, climate warming, changes in sea level and a combination of some of these factors. Indeed, it has been shown that increased sedimentation correlates well with rapid mangrove accretion in New Zealand through the emergence of additional mangrove habitat space, but the effect of the nutrient uploads has received less attention. Additionally, there is almost no information on the salinity levels that are characteristic for temperate New Zealand mangrove ecosystems. Indeed, it is well documented that salinity is an important controlling factor for mangrove growth in tropical mangrove ecosystems, but there is almost no such studies in temperate mangrove areas. Current research is highly relevant to on-going controversial discussions regarding management versus conservation of New Zealand mangroves, because it provides the review and experimental work on the cycling of nutrients in temperate mangrove and ecosystems as well as how salinity levels affect mangrove growth. This study presents previously missing information on the sources of nutrients in New Zealand estuarine ecosystems, as well as how these nutrients are conserved and stored in below ground biomass of A. marina. Field fertilisation experiments were conducted to describe nutrient availability as a primary driver for the difference in growth forms of mangrove plants (tall plants at the edge and stunted inland) in temperate New Zealand conditions. Controlled laboratory experiments were conducted to demonstrate how nutrient availability changes metabolite profiles of individual mangrove plants. The present research also provides novel information on how seasonal changes in salinity distribution patterns across the intertidal gradient in temperate mangrove ecosystems affect sodium composition of mangrove leaves. Results of the growth trial also suggest that moderate salinity has beneficial effects on A. marina seedling growth. Overall, results suggest that a unique combination of factors can increase growth and spread of temperate mangroves in estuarine and coastal territories in northern New Zealand. One of the most important factors is the cooler and wetter New Zealand climate, which is, due to high precipitation rate and low temperature. These conditions result in lower salinity levels, which are beneficial for A. marina growth. Another factor impinging on these mangroves is the natural nutrient deficiency state of these coastal ecosystems, and anthropogenic influences. These anthropogenic influences are mainly due to the increasing nutrient input over the past 100 years, originating from fertilisation, livestock urine runoff from dairy and meat farming, and human sewage inputs, which promotes growth and survival of mangrove seedlings. In addition, it can be concluded that the presence of mangrove plants at the interface between anthropogenically affected terrestrial lands and coastal ecosystems may mangrove habitats may act as nutrient sinks, thus mitigating coastal and marine eutrophication.
Keywords: Mangroves; Plant growth; Nutrients; Salinity